2012
DOI: 10.1155/2012/303565
|View full text |Cite
|
Sign up to set email alerts
|

Moral Foundation of the Kindergarten Teacher’s Educational Approach: Self-Reflection Facilitated Educator Response to Pluralism in Educational Context

Abstract: This paper investigates the moral foundation of Kindergarten teachers’ educational approach from the perspective of sensitivity towards religions and other worldviews. As a context for the examination, the paper presents the current situation of the Finnish multi-faith kindergartens through the empirical mixed method data gathered from five day care centres in the capital Helsinki area. The findings illustrate that at present, the multitude of religions and other worldviews in the increasingly diverse Kinderga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 10 publications
1
29
0
2
Order By: Relevance
“…This reaction confirms the findings in studies of religiously diverse Finnish ECECs (Kuusisto, 2011;Kuusisto & Lamminmäki-Vartia, 2012). Kuusisto (2011) found that in the case of four multicultural ECECs studied, the staff had become "exceedingly sensitive to any hints of religion in order not to offend anyone" (p. 119).…”
Section: Religion and Traditionsupporting
confidence: 78%
See 2 more Smart Citations
“…This reaction confirms the findings in studies of religiously diverse Finnish ECECs (Kuusisto, 2011;Kuusisto & Lamminmäki-Vartia, 2012). Kuusisto (2011) found that in the case of four multicultural ECECs studied, the staff had become "exceedingly sensitive to any hints of religion in order not to offend anyone" (p. 119).…”
Section: Religion and Traditionsupporting
confidence: 78%
“…Studies on ECECs in Finland (Kuusisto & Lamminmäki-Vartia, 2012) and Norway have concluded that ECEC teachers perceive religious diversity as more of a challenge than cultural diversity (which they can address through topics such as language, food, and ethnicity). Statements from teachers in the examined ECEC imply the same result.…”
Section: Religion and Traditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that teachers tend to be ignorant about parents' wishes and beliefs on matters such as religion or food (e.g., Tobin & Kurban, 2010). In the Finnish ECEC, uncertainty was noted on the implementation of religions and worldviews, and some personnel had difficulties with incorporating different religions (Kuusisto & Lamminmäki-Vartia, 2012).…”
Section: Promoting Cultural and Linguistic Diversitymentioning
confidence: 99%
“…Saila Poulter et al (2015) have examined different perspectives on the concepts of worldview and religion in the context of multicultural education. And Kuusisto and Lamminmäki-Vartia (2012) have looked at the moral foundation of the Finnish KTE and compared it with empirical findings from kindergartens in Finland.…”
Section: Introductionmentioning
confidence: 99%